The genus Maracarus (Acari: Halacaridae), description of three new species and one new record from Türkiye - Durucan, Furkan (Zootaxa, 2024)
Three new and one previously known species belonging to the halacarid mite genus Maracarus Bartsch, 2016 are described on the basis of the specimens collected from fine and medium coarse sand sediment from Muğla and Antalya, Türkiye. The new species, Maracarus almiri n. sp., Maracarus pedroi n. sp., and Maracarus terueae n. sp., are found to belong to the gracilipes group. Additionally, previously known species Maracarus gracilipes (Trouessart 1888) is reported for the first time from Turkish coast.